Comparing perilymph proteomes across species - Palmer,JC; Lord,MS; Pinyon,JL; Wise,AK; Lovell,NH; Carter,PM; Enke,YL; Housley,GD; Green,RA (Laryngoscope, 2018)
© 2017 The American Laryngological, Rhinological and Otological Society, Inc. Objectives/Hypothesis: Biological components of perilymph affect the electrical performance of cochlear implants. Understanding the perilymph composition of common animal models will improve the understanding of this impact and improve the interpretation of results from animal studies and how it relates to humans. Study Design: Analysis and comparison of the proteomes of human, guinea pig, and cat perilymph. Methods: Multiple perilymph samples from both guinea pigs and cats were analysed via liquid chromatography with tandem mass spectrometry. Proteins were identified using the Mascot database. Human data were obtained from a published dataset. Proteins identified were refined to form a proteome for each species. Results: Over 200 different proteins were found per species. There were 81, 39, and 64 proteins in the final human, guinea pig, and cat proteomes, respectively. Twenty-one proteins were common to all three species. Fifty-two percent of the cat proteome was found in the human proteome, and 31% of the guinea pig was common to human. The cat proteome had similar complexity to the human proteome in three protein classes, whereas the guinea pig had a similar complexity in two. The presence of albumin was significantly higher in human perilymph than in the other two species. Immunoglobulins were more abundant in the human than in the cat proteome. Conclusions: Perilymph proteomes were compared across three species. The degree of crossover of proteins of both guinea pig and cat with human indicate that these animals suitable models for the human cochlea, albeit the cat perilymph is a closer match. Level of Evidence: NA. Laryngoscope, 128:E47–E52, 2018.